Investigation of Natural Compounds for Therapeutic Potential in Streptozotocin-induced Diabetic Neuroinflammation and Neuropathic Pain - Faheem, Muhammad; Khan, Arif-ullah; Shah, Fawad Ali; Li, Shupeng (Frontiers in Pharmacology, 2022)
Diabetic neuropathy (DN) is microvascular complication of diabetes mellitus (DM) that impacts nervous system. The current research explored neuroprotective berbamine bergapten and carveol on DM-induced neuroinflammation and neurodegeneration causing neuropathic pain. The study was initiated with utilization of computational analysis (docking assay and molecular dynamic simulation study) before moving to the in-vivo protocols. The diabetic neuropathy was induced by intraperitoneal injection of streptozotocin (65 mg/kg) and animal were kept for development of diabetic neuropathy for 4 weeks. Once diabetic neuropathy was confirmed, all animals were subjected to treatment with berbamine bergapten and carveol and preceded till 6th weeks (two weeks of treatment). At 6th weeks after STZ administration rats were sacrificed, sciatic nerve and spinal cord were collected for molecular investigation. The docking and molecular dynamic simulation (MDS) delivered the information that natural compounds (Berbamine bergapten and carveol) were interacting with the selected target protein (mitogen activated protein kinase). Berbamine bergapten and carveol without affecting blood glucose level ameliorate mechanical allodynia and thermal hyperalgesia on 28th day of the study (two weeks after treatment). Berbamine bergapten and carveol markedly elevated the levels of glutathione (GSH), glutathione s-transferase (GST) and in both sciatic nerve and spinal cord and diminished lipid peroxidase (LPO) and nitric oxide (NO). The mentioned natural isolates reduced pathologic alterations provoked through DN, which was confirmed through histopathological assays (hematoxylin and eosin staining and Immunohistochemical analysis). Treatment down regulated the higher expression of the inflammatory mediatorcyclooxygenase-2 (COX-2), tumor necrosis factor-α (TNF-α) and nuclear factor kappa B (NF-Κb) confirmed by elisa and polymerase chain reaction (PCR). The outcomes of berbamine bergapten and carveol are compared with the pregabalin as positive control group. Treatment with mentioned three natural compounds improved nociception and reduced hyperalgesic effects compared to pregabalin and consequently reduced pain perception and inflammation. Our results suggest conceivable mechanism of berbamine bergapten and carveol for the neuro-protective impact possibly might be arbitratedviaCOX-2, TNF-α and NF-κB and regulated by mitogen activated protein kinase eventually ameliorating STZ provoked DM-induced neuroinflammation and neurodegeneration associated neuropathic pain.